Efficacy of an artificial pancreas device for achieving tight perioperative glycemic control in living donor liver transplantation. Issue 3 (15th November 2018) - Soyama, Akihiko; Kugiyama, Tota; Hara, Takanobu; Hidaka, Masaaki; Hamada, Takashi; Okada, Satomi; Adachi, Tomohiko; Ono, Shinichiro; Takatsuki, Mitsuhisa; Eguchi, Susumu
Abstract: Intraoperative hyperglycemia during liver transplantation can induce infectious bacterial complications after surgery. The aim of this study was to evaluate the efficacy of the artificial endocrine pancreas in achieving perioperative blood glucose control and preventing infection in patients undergoing living donor liver transplantation (LDLT). We compared 14 patients with an artificial endocrine pancreas device to 14 patients who underwent glycemic control using the sliding scale method with respect to perioperative blood glucose level and postoperative infection. In this study, we aimed to control the perioperative glucose levels consecutively for 24 hours from the induction of anesthesia. The average blood glucose level in the artificial pancreas group was significantly lower than that in the sliding scale group (118 vs. 141 mg/dL, P  < 0.05). The postoperative bacterial infection rate of the artificial pancreas group was significantly lower than that of the sliding scale group within one month after LDLT (35.7% vs. 78.6%, P  < 0.05). Multiple regression analysis showed non‐application of artificial endocrine pancreas as a significant risk factor of posttransplant infection. The artificial endocrine pancreas enabled the perioperative glucose level to be stably controlled without hypoglycemia. Artificial pancreas may reduce the incidence of postoperative infection after LDLT.